Measuring IT-Business Strategic Alignment in Indonesian Digital Start-ups - Fachri, Barany; Iqbal, Muhammad; Supiyandi; Hasanuddin, Muhammad (CV Raskha Media Group, 2025)
This study investigates the level of strategic alignment between Information Technology (IT) and business in digital start-ups across Java, Indonesia, using Luftman’s Strategic Alignment Maturity (SAM) model as the primary analytical framework. A mixed-methods approach was employed, combining quantitative data from structured questionnaires with qualitative insights from interviews involving supervisors from IT and business divisions. The findings indicate that digital start-ups have achieved a moderate level of alignment maturity, corresponding to the Established Focused Process stage, with an average score of 3.45. Partnership and technology scope emerged as the most mature domains, demonstrating effective collaboration and technological adaptability. In contrast, governance and competency measurement were identified as areas requiring significant improvement. The results highlight that alignment in these organizations is largely driven by informal relationships, entrepreneurial culture, and shared innovation values rather than by formal governance systems. Strengthening IT governance, implementing structured performance metrics, and promoting cross-functional skill development are recommended to advance alignment maturity. This research contributes to the broader understanding of IT-business integration in emerging digital economies and provides a practical framework for improving strategic coherence and organizational performance in start-up environments.